1991
DOI: 10.1111/j.1365-3091.1991.tb01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Depositional sequences and correlation of middle(?) to late Miocene carbonate complexes, Las Negras and Nijar areas, southeastern Spain

Abstract: During Serravallian through Messinian time, marine carbonates flanked topographic highs that rimmed Neogene basins in the Western Mediterranean. Middle to upper Miocene carbonate strata in the Las Negras and Nijar areas (southeastern Spain) are 50‐150 m thick and display 50‐200 m of shelf‐to‐basin relief over 1‐2 km. Detailed studies in those areas document the effects of relative sea‐level change on sedimentation, biotic composition, and reef development. We identify three previously unrecognized, regionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 22 publications
(44 reference statements)
3
39
1
Order By: Relevance
“…Miocene shallow marine sediments are widely distributed around the Mediterranean, such as in Italy (Vecsei and Sanders, 1999), Spain (Franseen and Mankiewicz, 1991;Pomar, 1991;Pomar et al, 2004) and Southern Turkey (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Miocene shallow marine sediments are widely distributed around the Mediterranean, such as in Italy (Vecsei and Sanders, 1999), Spain (Franseen and Mankiewicz, 1991;Pomar, 1991;Pomar et al, 2004) and Southern Turkey (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, many additional outcrops of BRC have been found to the southwest of Carboneras in the areas of Mesa Roldµn, Ricardillo and Agua Amarga Hultzsch 1999;Brachert et al 2001). Earlier works by Melendez et al (1964), Saavedra (1966), FustØr et al (1967), Zeck and Soediono (1970), Franseen and Mankiewicz (1991) and Serrano (1992) have documented neptunian dikes and volcaniclastic breccia/conglomerate attributable to the BRC from various areas of the Níjar-Carboneras Basin, which suggest an original distribution much more widespread than originally perceived, and which calls into question the original olistostrome model. Second, Franseen et al (1993) have shown that some concentric and polygonal cracks within the volcanic substrate are related to subaerial weathering.…”
Section: Introductionmentioning
confidence: 92%
“…Rotations in the orientation of stresses caused the NE-SW fault systems to change from dominantly reverse displacements (Tortonian and late Pliocene to Holocene) to sinistral wrench displacements (late Tortonian-early Pliocene; de la Chapelle 1988; Montenat et al 1990). The distribution of local depocenters within the Carboneras subbasin, such as in the areas of Agua Amarga (Martin et al 1996) or Las Negras (Franseen and Mankiewicz 1991), corresponds with uplifted and subsided blocks defined by an array of faults which strike NW-SE and NE-SW ( Fig. 1; Brachert et al 2002).…”
Section: Structural Settingmentioning
confidence: 98%
“…Beach and shoals facies show the same compositional and textural characteristics of the silicilastic skeletal F5b and terrigenous sand (F5a) of the Pontian shelf. Franseen and Mankiewicz (1991) illustrated Upper Miocene siliciclastic-carbonate deposits from Las Negras and Nijar (Southeastern Spain). The facies model presented by these authors show a general increase basinward in finegrained wackestone/packstones and a shelfward increase in red algae-rich packstone and coarse-grained packstone/ grainstone with a discrete increase of terrigenous (siliciclastic and vulcanoclastic sediment) material in the near-shore environment.…”
Section: Comparison With Other Mixed Systemsmentioning
confidence: 99%